DEVELOPING CULTURE-BASED SUPPLEMENTARY READING MATERIAL FOR THE EIGHTH GRADE STUDENTS OF SMP LABORATORIUM SINGARAJA - ., IDA AYU MADE ISTRI UTAMI; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Universitas Pendidikan Ganesha, 2014)
Penelitian ini bertujuan untuk mengembangkan materi tambaha membaca berbasis budaya dimana subjek dari penelitian ini adalah siswa kelas VIII SMP Laboratorium Undiksha Singaraja. Tujuan penelitian ini adalah mengidentifikasi potensi dan masalah dalam membaca yang dihadapi oleh siswa, mendeskripsikan materi membaca berbasis budaya untuk siswa, dan menganalisis kualitas materi membaca berbasis budaya untuk siswa yang dikembangkan. Model pengembangan yang digunakan dalam penelitian ini adalah model Penelitian dan Pengembangan yang diadaptasi dari model oleh Sugiyono (2011) dan berdasarkan kriteria materi membaca yang baik oleh Tomlinson (1998). Deskripsi materi membaca berbasis budaya untuk siswa kelas delapan Sekolah Menengah Pertama dijabarkan ke dalam empat aspek: konstruksi, isi, penggunaan bahasa, penampilan, dan kegiatan membaca. Uji validitas dalam penelitian ini menunjukkan prototipe yang dievaluasi berkualitas sangat baik dengan skor rata-rata 4,58. Uji kegunaan menunjukkan bahwa siswa berlaku sangat baik dan aktif dalam implementasi materi tambahan membaca berbasis budaya. Kata Kunci : materi membaca, budaya, penelitian dan pengembangan This Research and Development aimed at identifying the potentials and problems in reading in EFL classes, describing the outlook of a well developed culture-based supplementary reading material, and analyzing the quality of the newly developed culture-based supplementary reading material for the eighth grade students of Junior High School. Following the seven steps suggested in Sugiyono model, This study was based on the result of the preliminary observation which showed that there was a need to develop reading material which contains some cultural aspects in it. This research employed Research and Development model adapted from Sugiyono (2011). The first finding identified topic selection, pictures or illustration and kind of reading activities as the problems in reading and they were used as the consideration in identifying the potentials in developing reading material. A well developed culture-based supplementary reading material can be described from five aspects: construction, content, language use, physical appearance, and reading activities. Finally, the validity was measured from the score given by all experts. The prototype can be categorized as having Excellent quality as indicated by the mean score of 4.58 in which the Sr < 4.485. In addition, the result of observation showed that the students were doing excellent during the implementation of culture-based supplementary reading material.keyword : reading material, culture, Research and Development